Interpretation of sustainability in the utilization of renewable energy sources - Dombi, Mihály; Kuti, István; Balogh, Péter (Acta Agraria Debreceniensis, 2011)
The utilization of renewable energy sources (res) is crucial regarding to sustainable reconstruction of energy systems. The target is a balanced, sustainable development of Hungarian energy management considering equally the ecological, social and economic aspects. There are many different technologies of utilization of res varied by sources, conversion processes, size and products. The comparison of each technology and their sustainability assessment are required by the importance of efficient remodeling of energy infrastructure. The group of attributes was composed by numerous important parameters in the course of our analysis with the choice experiment (ce) methodology. The estimation of each attributes’ influence on the individual’s preferences and choices was possible by this method and the preferences of the statistical population was concluded. So thus the utility derived from each attribute was estimated. The result of the ce analysis for the population of experts is demonstrated in the current phase of our research.